Central Nervous System Tumours—- A Study of Frequency and Morphology - TANYA DOGAR ASMAA QURESHY NAVID QURESH, ROZINA JAFFAR (Journal of Fatima Jinnah Medical University, 2018)
Background: Owing to the confined space in the intra-cranial cavity,brain tumours even if benign can have life-threatening consequences. Malignant brain tumours can be widely invasive and infiltrative. Objective: To study the incidence, frequency and morphological patterns of CNS tumours. Method: A retrospective study of all cases of brain tumours received at Pathology Department PGMI was carried out from 1.1.2009 to 31.12.2010 . Results: A total of 96 cases of CNS tumours were studied during a period of two years.The morphological distribution was as follows : meningioma 18 (18.8%), glioblastoma multiforme 8 (8.3%), anaplastic astrocytoma 16 (16.7%), astrocytoma 12 (12.5%), pilocytic astrocytoma 2 (2.1%), oligodendroglioma 6 (6.3%), ependymoma 4 (4.2%), mixed glioma 4 (4.2%), schwannoma 8 (8.3%), craniopharyngioma 6 (6.3%), pituitary adenoma 6 (6.3%),haemangioblastoma 2 (2.1%) and metastases 4 (4.2%).64 cases (66.7%) occurred in males and 32 cases (33.3%) in females.80 (83.3%) patients were adults while 16 (16.7%) were children. Conclusion: CNS neoplasms are diverse in their morphology and grade.Histological examination of H&E stained sections enables diagnosis,classification and grading. In some cases, special stains and immunohistochemistry may be required. Correlation of histological examination with radiological findings ( CT and MRI ) and clinical data is essential.